The Implementation of Siri Na Pacce Culture in Bugis-Makassar Wedding in Bissoloro Village, Bungaya District, Gowa Regency - Rahmawati Harisa (Journal of Research and Multidisciplinary, 2022)
Siri' Na Pacce is not something new for the Bugis-Makassar community. Even the Siri 'Na Pacce culture existed in the royal era before Islam entered Sulawesi. This paper uses a qualitative method using an anthropological, sociological, and religious approach. The Siri' Na Pacce culture from the beginning was known for the emphasis on personality in relationships with others as a good moral image. In Bugis-Makassar culture, someone who does not have Siri' Na Pacce, then his attitude and nature are the same as animals. The implementation of Siri' Na Pacce values in the marriage of the Bissoloro Village community includes high solidarity, respect for local culture, and sensitivity to others. Uang Panai is not known in Islamic teachings, there is only a dowry. In the tradition adopted by the Bugis-Makassar community, if we are based on the values of Siri' Na Pacce Uang Panai that is given by men to women is a form of appreciation and gratitude to women's parents before transferring the responsibilities of their daughters.